Assessment of breast cancer risk perception, knowledge, and breast self-examination practices among market women in Owo, Ondo State, Nigeria - Mujidat Awogbayila; Olayinka Onasoga; Umar Jibril; Funmilayo Oluwafemi; Edidiong Orok (BMC, 2023)
Abstract Background Breast cancer (BC) is the leading cause of cancer death among women worldwide, and its incidence is increasing, particularly in low-medium-income countries (LMICs). Evidence shows that breast self-examination (BSE) is culturally acceptable, religiously friendly and inexpensive. This study assessed BC risk perception, knowledge and breast self-examination practices among market women in Ondo State, Nigeria. Methods A descriptive cross-sectional survey was conducted among market women in 3 selected markets in Owo. A semi-structured interview-based questionnaire was used to collect data. The instrument consisted of five sections based on the objective of the study. Selection of the study participants was done using a multistage sampling technique. The test-retest method was used to determine the reliability of the instrument. Participants knowledge and practices were categorised into good (≥ 50% total score) and poor (< 50% total score) while risk perception was grouped into high (≥ 50% total score) and low (< 50% total score).Data were analysed using descriptive and inferential statistics at a p value < 0.05 for determining statistical significance. Results A total of 335 respondents completed the study and the mean age ± S.D. was 37.19 ± 9.19 years (range: 18-65 years). 47.5% of respondents were Christian while 60.0% of the respondents were married. 15.5% had tertiary education, and more than two-thirds were from the Yoruba tribe. More than two-thirds (78.5%) of the participants stated that they practiced breast self-examination, while 58.5% reported to have been taught how to perform BSE. 75.8% agreed that the use of injectable contraception or oral pills can result in BC, while 75.8% also agreed that women of reproductive age are at risk of BC. Less than 50% mentioned that they were uncomfortable taking off clothes in front of health professionals during the examination. The perceived risk of BC showed that 221 (65.97%), and 114 (34.03%) of respondents had high, and low levels of perceived risk of BC, respectively. However, 184 (54.93%) and 151 (45.07%) of the respondents had good and poor knowledge. The majority (139, 41.49%) of the respondents had poor BSE practice. Age (p = 0.023), educational qualifications (p < 0.001), average income per month (p < 0.001) and ethnicity (p =  < 0.001) were statistically associated with knowledge of breast self-examination while religion (p = 0.02), marital status (p = 0.01), educational qualification (p = 0.001) and distance from facility (p = 0.009) were statistically associated with perceived risk of BC. Participants' educational qualification (p = 0.006) and ethnicity (p = 0.013) were statistically associated with practice of BSE. Good knowledge was also identified as a significant predictor of good practice of participants among the women (95%CI: 4.574 (2.841-7.365), p < 0.001). Conclusion This study identified high level of perception, good knowledge and good practice of BSE among majority of the market women in Owo Town. Interventions and extensive health education on BSE with the aim of creating positive awareness and understanding of BSE among the population should be encouraged.